2015
DOI: 10.1080/14772000.2015.1046967
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of the hypotrichous ciliate Uncinata, with descriptions of the morphology and phylogeny of three urostylids (Protista, Ciliophora)

Abstract: Song (2015) Redefinition of the hypotrichous ciliate Uncinata, with descriptions of the morphology and phylogeny of three urostylids (Protista, Ciliophora), Systematics and Biodiversity, 13:5, 455-471,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…According to this detailed revision, Family Urostyloidea includes about 34 valid genera and 154 valid species. In recent years, several new species were added to this family, which suggested that the diversity of this family of ciliates was under-estimated (e.g., Chen et al, 2011Chen et al, , 2013Fan et al, 2015Fan et al, , 2016Foissner and Stoeck, 2008;Hu et al, 2015;Jo et al, 2015;Jung et al, 2011Jung et al, , 2015Luo et al, 2015;Lv et al, 2015;Paiva et al, 2016;Shao et al, 2008a, b;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to this detailed revision, Family Urostyloidea includes about 34 valid genera and 154 valid species. In recent years, several new species were added to this family, which suggested that the diversity of this family of ciliates was under-estimated (e.g., Chen et al, 2011Chen et al, , 2013Fan et al, 2015Fan et al, , 2016Foissner and Stoeck, 2008;Hu et al, 2015;Jo et al, 2015;Jung et al, 2011Jung et al, , 2015Luo et al, 2015;Lv et al, 2015;Paiva et al, 2016;Shao et al, 2008a, b;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Classification and terminology follow Berger (, ) in general and partially follow Luo et al. () for the genus Holosticha .…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies (Berger 2003(Berger , 2006Luo et al 2015), the genus Holosticha Wrzesniowski, 1877 is composed of seven species: H. diademata (Rees, 1884) Kahl, 1932; H. foissneri Petz et al, 1995;H. gibba (M€ uller, 1786) Wrzesniowski, 1877; H. hamulata Lei et al, 2005; H. heterofoissneri Hu and Song, 2001;H.…”
mentioning
confidence: 99%
“…; Luo et al. ; Paiva and Silva‐Neto ; Singh and Kamra ). Moreover, some recent phylogenetic analyses have led to a better understanding of systematics and evolutionary relationships (e.g., Bourland ; Chen et al.…”
mentioning
confidence: 99%
“…FOR a long time, a high degree of morphological variation and adaptation and diverse morphogenetic characteristics has brought great challenges to the taxonomy of hypotrichous ciliates. However, many new inventories have been achieved from some under-sampled or insufficiently investigated biotopes in the last decade (e.g., Chen et al 2015a;Fan et al 2014a,b;Foissner and Stoeck 2008;Foissner et al 2010;Gupta et al 2006;Heber et al 2014;Hu and Kusuoka 2015;Jung et al 2014Jung et al , 2015Kim et al 2014;Kumar et al 2014Kumar et al , 2015K€ uppers 2014;Lu et al 2014;Luo et al 2015;Paiva and Silva-Neto 2009;Singh and Kamra 2015). Moreover, some recent phylogenetic analyses have led to a better understanding of systematics and evolutionary relationships (e.g., Bourland 2015;Chen et al 2014Chen et al , 2015bFan et al 2015;Huang et al 2014;Lv et al 2015;Spakova et al 2014;Wang et al 2015;Yi and Song 2011;Zhao et al 2015).…”
mentioning
confidence: 99%